The tale of two stones in an obstructed partial duplex kidney: case presentation - Yusof, M. R.; M.S., Fairuz; Lee, F. Y.; V. J., Arvind; O., Fahmy; Lee, C. K.; M. Z., Saiful Azli; A. P., Arunasalam; M., Khairul Asri (PubMed Central International, 2022)
Duplex renal systems is a common anomalies. Incidence rate of 0.8% in healthy adult population and 2-4% in patients investigated for urinary tract symptoms. Urolithiasis management for patients with anomalies is complex and require proper imaging and planning. We have a patient with a partial duplex collecting system presented with a right renal calculus in a non-functioning lower moiety and multiple distal ureteric calculi. Preoperative planning done and surgery performed with good outcome without any early and late complications.